PERAN PEKERJA SOSIAL DALAM MENGATASI PERMASALAHAN REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA TARUNA JAYA 1 - Mayaut, Flores George; Yatinah, Yatinah (Jurnal Insani, 2021)
This writing discusses the role of social workers in overcoming the problems of school dropouts at the Taruna Jaya Youth Development Institution 1. This research is descriptive-analytical, with the aim of obtaining an overview of the role of social workers in overcoming the problems of school dropouts. In this writing, the author determines three cases that have been determined purposively. The case was taken from 3 cases that had been handled at the Taruna Jaya 1 Youth Development Institution. The problems of teenagers dropping out of school at the orphanage are: Lack of love from parents; the client's lack of spiritual level; clients dropping out of SMK class 2; ex-street child/punk clients who are used to consuming illegal drugs and drinking and smoking; clients drop out of school because of the economic factors of their parents; the client does not have a job; clients rarely carry out Worship. The roles performed are the role of broker, counselor, mediator, motivator, educator, and facilitator. The result is that the client's family (grandmother) is happy to receive news about the existence of EP, the client has been actively participating in the obligatory congregational prayers and learning the Koran, the client is already on the list of pursuing package C, the client is willing to undergo outpatient treatment from the DKI Jakarta BNN and stop consuming drugs and cigarettes, clients are enthusiastic about participating in activities at the orphanage, clients are diligent in entering skills classes majoring in refrigeration AC, clients are ready to take part in the PBK program (work-learning practice).